Saliva and its role in the transmission of covid-19 - what the dentist needs to know - Rocafuerte Acurio, Marco (2020)
The COVID-19 is an infectious disease caused by a new type of coronavirus which has been recently discovered. This virus is spread mainly through droplets of saliva or discharged from the nose when an infected person coughs or sneezes and this is an alert for all the dentists. For that reason, a relevant research has been done on this matter in order to determine the risk of the saliva of a patient infected with COVID-19 (symptomatic or asymptomatic), as well as its mechanism of transmission and the potential for contagion to which oral health professionals are exposed.